2018
DOI: 10.7717/peerj.4403
|View full text |Cite
|
Sign up to set email alerts
|

Similar acute physiological responses from effort and duration matched leg press and recumbent cycling tasks

Abstract: The present study examined the effects of exercise utilising traditional resistance training (leg press) or ‘cardio’ exercise (recumbent cycle ergometry) modalities upon acute physiological responses. Nine healthy males underwent a within session randomised crossover design where they completed both the leg press and recumbent cycle ergometer conditions. Conditions were approximately matched for effort and duration (leg press: 4 × 12RM using a 2 s concentric and 3 s eccentric repetition duration controlled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 97 publications
0
13
1
Order By: Relevance
“…On average the ratings of perceived effort reported in the present study were around ~1 point lower than those reported by , though in their study the exercise protocols were designed to be high, but not necessarily maximal. Despite this, in the present study participants perceptions of discomfort were around ~2-3 points higher than those reported by Steele et al (2018). This suggests the possibility of an exponential increase in discomfort when efforts are near maximal in both exercise modailities, but that this response may be similar between them.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…On average the ratings of perceived effort reported in the present study were around ~1 point lower than those reported by , though in their study the exercise protocols were designed to be high, but not necessarily maximal. Despite this, in the present study participants perceptions of discomfort were around ~2-3 points higher than those reported by Steele et al (2018). This suggests the possibility of an exponential increase in discomfort when efforts are near maximal in both exercise modailities, but that this response may be similar between them.…”
Section: Discussioncontrasting
confidence: 87%
“…The comparative strength adaptations may result from similar neuromuscular stimulus in both modalities when effort and duration are analogous. Both Steele et al (2018) and Kuznetsov et al (2011) have reported findings suggesting that motor unit recruitment may be similar between modalities and indeed effort has been argued to arise from the central motor command required to drive the musculature to perform the task being attempted (Marcora, 2009;Pageaux et al, 2016). Thus, it is thought that effort, both that required and perceived, is likely intrinsically linked to motor command and motor unit recruitment (de Morree et al, 2012;Guo et al, 2017) and possibly due to Henneman's size principle (Potvin and Fuglevand, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They examined the oxygen uptake responses between the two modalities finding no differences and concluded that the manner of exercise performance, and not the modality, was likely the primary determinant of this physiological response. More recently, Steele et al (2018) compared the acute response of lower body “cardio” (recumbent cycle ergometry) to resistance exercise (leg press) during high intensity of effort tasks, matched for effort and duration (4 × 60 s sprints for “cardio” and 4 × 12 repetition maximum for resistance exercise with time matched using a 2 s concentric and 3 s eccentric repetition duration). They considered a range of physiological responses including oxygen consumption, respiratory exchange ratio, blood lactate, estimated energy expenditure, muscle swelling, and electromyography finding no differences between the modalities for any outcome.…”
Section: Effort and Duration Matched Modality Comparisonsmentioning
confidence: 99%
“…They considered a range of physiological responses including oxygen consumption, respiratory exchange ratio, blood lactate, estimated energy expenditure, muscle swelling, and electromyography finding no differences between the modalities for any outcome. Steele et al (2018) examined only amplitude based electromyographical variables but Noble et al (2019) have also examined normalized (to % max) electromyographic amplitudes, which appear to be greater during typical resistance training (single leg knee extension) compared with “cardio” mode (single leg cycle ergometry) exercise performed to volitional failure. Unlike Steele et al (2018), time to task failure in Noble et al (2019) was unclear and thus, it is unknown if it was similar between conditions.…”
Section: Effort and Duration Matched Modality Comparisonsmentioning
confidence: 99%